Vulnerability Assessment and Enhanced Community-based Care and Management of Patients With Tuberculosis in Korea: A Crossover Design - Seo, Jeongmi; Jeong, Dawoon; Lee, In-Hyuk; Han, Jiyeon; Kwon, Yunhyung; Shim, Eunhye; Choi, Hongjo (Journal of preventive medicine and public health, 2025)
Objectives: People-centered care and social protection are critical for improving tuberculosis (TB) treatment outcomes. This study aimed to evaluate whether a vulnerability assessment tool, developed for an enhanced community-based care and management (ECCM) program in 2 Korean cities, could predict and improve final TB treatment outcomes based on patients’ vulnerability levels.Methods: Treatment outcomes in the ECCM group were compared with those in a control group, stratified by vulnerability level. During stage 1, one city served as the intervention region and the other as the control, with a crossover in stage 2. The vulnerability assessment included all notified patients with TB, and those identified as highly vulnerable in the intervention group received social support following a consultation with a case manager.Results: The vulnerability assessment tool demonstrated moderate predictive ability for unfavorable outcomes, with an area under the curve of 0.70 (95% confidence interval, 0.63 to 0.77). The patients with high vulnerability who received ECCM treatment demonstrated a 19.8-percentage point (%p) higher treatment success rate than the high vulnerability subcategory of the control group. ECCM also appeared to reduce loss to follow-up and TB-related mortality by 8.4%p and 7.3%p, respectively, although these findings should be interpreted with caution.Conclusions: The results suggest that providing social support tailored to patient vulnerability at the time of diagnosis could improve TB treatment outcomes.